183 A phase 1B/2A trial of tofacitinib, an oral janus kinase inhibitor, in systemic lupus erythematosus. (April 2019) - Hasni, Sarfaraz; Gupta, Sarthak; Davis, Michael A; Poncio, Elaine; Temesgen-Oyelakin, Yenealem; Biehl, Ann; Carlucci, Philip; Wang, Xinghao; Ochoa-Navas, Isabel; Manna, Zerai G; Naqi, Mohammad; Shi, Yinghui; et al.
Abstract : Background: A pharmacologic intervention that modulates JAK/STAT signaling pathways represents a novel approach for the treatment of Systemic Lupus Erythematosus (SLE). In animal models of SLE, tofacitinib improved clinical features, immune dysregulation and vascular dysfunction. The STAT4 risk allele is associated with higher risk of severe manifestations in SLE. We hypothesized that immune modulation in response to JAK/STAT inhibition would be more robust in SLE subjects that carry the STAT4 risk allele. Methods: We conducted a phase 1b/2a randomized, double-blind, placebo-controlled clinical trial of oral tofacitinib, 5 mg twice daily, in 30 SLE subjects (2:1 drug to placebo ratio) with mild to moderate disease activity, stratified by the presence or absence of STAT4 risk allele. Study duration was 84 days (56 days of active treatment ; 28 days of off drug). In addition to recording adverse events (AEs), lipoprotein profile, non-invasive vascular function studies, immuno-phenotyping, and gene expression studies were performed. Results: Tofacitinib was well tolerated with no worsening of SLE disease activity, and no severe AEs, opportunistic infections or liver function abnormalities. A total of 43 AEs (mostly mild respiratory infections) occurred in the treated group compared to 28 AEs in placebo. There was a significant increase in HDL-C and HDL particle size in tofacitinib-treated patients at day 56 (p=0.006) accompanied by significant improvements in plasma protein lecithin: cholesterol acyltransferase (LCAT) concentration. There were also trends for improvements in vascular stiffness in the tofacitinib-treated group. The Interferon response genes (type I IFN), the levels of low- density granulocytes (LDGs) and neutrophil extracellular trap (NET remnants) significantly decreased in the tofacitinib treated group who were STAT 4 risk allele positive but not in the placebo group at day 56, accompanied by significant changes in pSTAT phosphorylation of different immune cells. Levels of activation and checkpoint markers CD103, CXCR3, ICOS, and PD-1 were significantly decreased on multiple T cell subsets, in tofacitinib treated individuals that lack the STAT4 risk allele. Conclusions: In a short-term trial, tofacitinib was well tolerated in SLE subjects with mild-moderate disease activity. Use of tofacitinib resulted in improvements in lipoprotein profile and HDL function and decreases in the type I IFN and aberrant neutrophil responses characteristic of SLE. Long-term studies are needed to determine the efficacy of tofacitinib in the various manifestations of SLE. Funding Source(s): Intramural Research Program of the National Institute of Arthritis and Musculoskeletal and Skin Diseases of the National Institutes of Health and in part by Pfizer Inc. Adverse Events in Subjects on Tofacitinib vs Placebo